DrDMembangun Karakter Anak Usia Dini Melalui Metode Bercerita Untuk Anak Usia 5-6 Tahun Di Kelompok Bermain Getsemani Samarinda - Arrua, Serlyanti; Aslina, Yeni; Liana P, Heppy (Manajemen Pendidikan Program Doktor, 2024)
Character values are very important for students at the school level, especially for young children. One method that can be used to implement character education is storytelling. Therefore, this research was conducted with the aim of understanding how to build character and what strategies can be used to develop the character of children aged 5-6 years through storytelling using storybooks at KB Getsemani. This research employed a qualitative descriptive method, with data collected through interviews with classroom teachers, the principal, and parents. In addition to interviews, observations and documentation were also carried out to gather data. The analysis technique involved data reduction, data presentation, and drawing conclusions. Based on the research on building character education through storytelling for children aged 5-6 years at KB Getsemani, the results show that teachers have implemented storytelling methods along with certain steps. These steps were then evaluated using a rubric for assessing the implementation of storytelling in class. The results showed that 93% of the process aligned with the assessment guidelines. Moreover, the strategy used, namely the empirical learning strategy, also successfully influenced the children to remember and connect the activities with stories of goodness because it was done creatively and was not boring. From these results, it can be concluded that the application of the storytelling method and the use of empirical learning strategies succeeded in developing the character of children aged 5-6 years at KB Getsemani.